Best Answer

It is simple. Take conjugate 2 times. first treat root 2 and root 3 as a single term and do calculations. answer is (6*root2+4*root3-2*root30)/24

Q: How do you rationalise 1 over root 2 plus root 3 plus root 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

root 3 - 1 all over 2

the square root of (1/4) is 1/2

X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12

its going to be 4over 27 ----

1 over 2 plus 1 over 2= 2 over 2= 1 whole

Related questions

root 3 - 1 all over 2

Yes but not me

sqrt(1) + sqrt(1) + sqrt(64) = +/- 1 +/- 1 +/- 8 positive square root is 10 negative square root is -10 By permutating the +/- it could also be +8, -8 ,

Yes, if x and y = 1 √1 + √1 = √1 + 1 1 + 1 = 1 + 1 QED

square root of (x2 + 1) = no simplification (square root of x2) + 1 = x + 1

(a + b)*(a - b) = a2 - ab + ab - b2 = a2 - b2 The expression is often referred to as DOTS = Difference Of Two Squares. What is special about it is that the answer contains only the squares of the two terms while the cross-products cancel out. So (√6 + √5)*(√6 - √5) = (√6)2 - (√5)2 = 6 - 5 = 1 The above result is used to simplify surds and, in particular, to rationalise their denominators.

It already is in the form a+ib. a = root 7, the b=1 (i.e 1 x i ).

X^1/2 + Y^1/2 Essentially it is just the square root of x plus the square root of y, there's no real way of simplifying that.

Square root of 3 is approximately 1.732. 1.732 + 1 =2.732

1/8 plus 1/4 plus 1/2 = 7/8 or 0.875

the square root of (1/4) is 1/2

1/5 plus 1/7 plus 3/10 is equal to 0.642857